The Effect of Construction Cost Index, Investment, and Regional Budget Realization on The Performance of Indonesia's Construction Sector - Sonny Setyadhy; Pudji Astuty (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The construction sector plays a vital role in Indonesia's economic development, contributing significantly to national GDP and employment. However, the sector's performance has exhibited fluctuating trends in recent years, influenced by various macroeconomic and fiscal factors. This study aims to analyze the influence of the Construction Cost Index, Investment, and Regional Budget Realization on the performance of the Indonesian construction sector. The research employs a quantitative approach using panel data regression analysis. The sample comprises 20 provinces in Indonesia, observed over the period 2018 to 2023. The data utilized were sourced from Statistics Indonesia (BPS) and the Ministry of Finance. The results of the panel data regression analysis indicate that the Construction Cost Index, Investment, and Regional Budget Realization simultaneously have a significant effect on the performance of the construction sector. Partially, each independent variable also demonstrates a positive and significant influence. These findings suggest that increases in construction costs, investment flows, and the realization of regional government budgets are key determinants in driving the growth and performance of the construction sector across Indonesian provinces. The study underscores the importance of consistent and targeted fiscal policies to maintain the sector's momentum as a crucial engine of the national economy.